The comprehensive molecular landscape of the immunologic co-stimulator B7 and TNFR ligand receptor families in colorectal cancer: immunotherapeutic implications with microsatellite instability. (3rd October 2018) - Tang, Jinghua; Jiang, Wu; Liu, Dingxin; Luo, Jun; Wu, Xiaodan; Pan, Zhizhong; Ding, Peirong; Li, Yingqin
ABSTRACT: Immunotherapy is reportedly effective in a subset of colorectal cancers (CRCs) with high microsatellite instability (MSI-H). Exploring the expression patterns and clinical values of immunologic molecules is critical in defining the specific responsive candidates. Here, we performed comprehensive molecular profiling of the B7 and TNFR family genes across 6 CRC datasets with over 1, 000 patients' details using cBioPortal TCGA data. About 20% of patients had B7 and TNFR family gene alterations. The frequency of B7 gene mutations (2.2%–5%) were similar to copy number alterations (0.53%–5.46%). TNFR amplifications were relatively more common (5.45–11.32%) than that of B7 (0.09–2.73%). B7 and TNFR gene mRNAs were upregulated in 26% of cases (102/379) and 16% of cases (61/379), respectively. The mRNA levels of B7 and TNFR genes were inversely correlated with promoter methylation status. Clinically, both B7-H3 and TNFSF7 mRNA overexpression were associated with unfavorable clinical outcomes, and the B7-H3 expression was increased gradually in cases with gene amplifications. Moreover, patients with MSI-H had significantly higher PD-L1 or PD-1 expression. Most importantly, in MSI-H group, patients with PD-L1 or PD-1 upregulation had poorer survivals than those with PD-L1/PD-1 downregulation. This is the first study drawing the immune landscapes of the co-stimulator B7 and TNFR families in CRC and showing that MSI-H patients with PD-1/PD-L1 upregulation are associated with poor clinical outcomes, providing potential markers to stratify patients responsive to immune checkpoint therapy.